O princípio da segurança jurídica no direito administrativo brasileiro - Valim, Rafael Ramires Araujo (2009)
This study is intended to be a starting point to more in-depth investigations on the legal security principle under Brazilian Law. By sistematizing the content of the legal security principle under Brazilian Administrative Law, the aim is to bring out the full potential of this principle in order to provide maximum protection to the individuals and legal entities subject to this field of law. Merely enunciating the principle at issue in an ill-defined manner has increasingly become more trivial, and has given margin to exaggerations and, on other occasions, to undue restrictions to its application . These are the reasons why it is necessary to establish clear-cut boundaries of the legal security principle in the current legal system. Therefore, by means of a dogmatic analysis this study proposes a categorization of the legal security principle in two conceptual nuclei, which are: certainty and stability. To this end, from the standpoint of certainty the force, effectiveness and content of legal norms are addressed. And, from the point of view of stability we examine the doctrines of the vested right, the perfect juridical act and the res judicata, the sub-principle of the protection of legitimate trust, and its respective manifestations, and, finally, the concepts of limitation and lapse. In the words of Lopez de Oñate, the legal security principle represents the specific ethicality of the Law, and full compliance to the legal concepts that materialize this principle must be encouraged in order to prevent the rupture of the rule of law